Dímero D, ferritina, procalcitonina en procesos inflamatorios e infecciosos. RIOHOSPITAL, SC - Ibarra Apunte, Dayana Isabel (2023)
ABSTRAC In the present work, the relationship between the biomarkers D-dimer, ferritin, procalcitonin, in inflammatory and infectious processes of patients who attended the RIOHOSPITAL laboratory, SC. The research was descriptive,documentary, non-experimental, and cross-sectional, with a quantitative approach. The population was made up of 1320 patients, who underwent the analytes before mentioned, and the sample for 531 altered results of the same. With the analysis of the data obtained, it was observed that there were no marked differences between the total number of normal and abnormal results, but of the latter, ferritin was found to be elevated in a larger number of patients (192 cases). SARS COV-2 pneumonia was the most diagnosed pathology through the use of said analytes and the manifestations clinics that stood out were cough, malaise, dyspnea, headache, hypoxemia, pain chest, fever, weakness, corresponding these, with the entity mentioned previously. The most frequent age was in the group between 19 to 64 years and 65 years or further. D-dimer alterations predominated in the female sex, while ferritin and procalcitonin increased more in men. Regarding the ethnic groups, it was found the mestizo with the greatest presence in this investigation, so it would have a higher risk of contracting an infectious inflammatory process such as COVID-19, unlike the indigenous and white. From this investigation it is derived that the training and epidemiological surveillance to the population in order to prevent the spread of COVID-19. Keywords: Biomarkers, D-dimer, Ferritin, Procalcitonin, Pneumonia.